2015
DOI: 10.1089/scd.2014.0509
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell-Like Cells Set the Balance of Stimulatory and Inhibitory Signals in Monocyte-Derived Dendritic Cells

Abstract: The major reservoir of human multipotent mesenchymal stem/stromal cells (MSC) is the bone marrow (BM) with the capability to control hematopoietic stem cell (HSC) development. The regenerative potential of MSC is associated with enhanced endogenous repair and healing mechanisms that modulate inflammatory responses. Our previous results revealed that MSClike (MSCl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“… 28 In addition, MSCs can affect the dendritic cell (DCs) phenotype, cytokine release, differentiation and maturation, and weaken their antigen presentation ability. 29 Activated DCs produce a variety of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-12) and express high levels of co-stimulatory molecules (CD40, CD80, and CD86), thereby promoting the development of inflammation. Previous studies have noted the importance of DC maturation and activation in the progression of inflammation.…”
Section: Mechanism Of Mscs and Msc-exos In The Treatment Of Inflammat...mentioning
confidence: 99%
“… 28 In addition, MSCs can affect the dendritic cell (DCs) phenotype, cytokine release, differentiation and maturation, and weaken their antigen presentation ability. 29 Activated DCs produce a variety of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-12) and express high levels of co-stimulatory molecules (CD40, CD80, and CD86), thereby promoting the development of inflammation. Previous studies have noted the importance of DC maturation and activation in the progression of inflammation.…”
Section: Mechanism Of Mscs and Msc-exos In The Treatment Of Inflammat...mentioning
confidence: 99%
“…Recent evidence has suggested that adipose-derived MSCs may also have a more potent immunosuppressive effect in vitro than their bone marrow-derived counterparts IDO, PGE2, M-CSF, IL-6, IL-10, and TGF-b. IDO suppresses T and natural killer (NK) cells; PGE2 suppresses B cells and inhibits their differentiation into antibody-producing plasma cells [161], as well as prevent DC maturation in conjunction with M-CSF, IL-6, IL-10, and TGF-b [156,159,[162][163][164][165].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…It is known that the MSC cell line indirectly forces the differentiation of monocytes into CD1a − DC-SIGN + CD163 low CTLA-4 + semi-matured moDCs, whereas these cells directly promote the differentiation of CD1a − DC-SIGN low CD163 high M2 macrophage-like cells in a steady state [ 23 ]. Additionally, it is widely accepted that MSCs generally silence the inflammatory features of moDCs upon viral or bacterial infection [ 24 ].…”
Section: Introductionmentioning
confidence: 99%